Influence factors of photocatalytic activity of the filter media modified by TiO2 - Shen, Rongyan; Feng, Guoyong; Liang, Yuting; Zhao, Xingqing; Zhang, Wenyi (Hemijska industrija, 2014)
The gangue filter media was modified by the titanium dioxide (TiO2) through the liquid phase deposition method. Some influence factors of photocatalytic activity were investigated, including the mole ratio of initial solution, the water bath temperature, the deposition time, the calcination temperature, and the heat preservation time of calcination. The morphology of the film was examined by SEM, EDS, and crystallite structure by X-Ray Diffraction (XRD). The SEM, EDS, and XRD data showed that new TiO2 crystal was found in the modified filter media. And the specific surface area of the modified filter media greatly increased. By the orthogonal experiment, the optimum parameters of modification were (NH4)2TiF6:H3BO3=1:2, water bath temperature of 80?C, deposition time of 5h, calcination temperature of 500?C, and 1h heat preservation time of calcination. Under above conditions, the heavy nitrogen wastewater of 1589.94 mg/L COD and 18750 times chroma was treated by the modified filter media. After 1h catalytic reaction, the decolorization rate and COD removal rate reached 65.89% and 47.87%, respectively. nema